Folate Functionalized Lipid Nanoparticles for Targeted Therapy of Methicillin-Resistant Staphylococcus aureus - Kushal Vanamala (MDPI AG, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA), commonly called a superbug, is a highly alarming antibiotic-resistant population of Staphylococcus aureus (S. aureus) bacteria. Vancomycin (VAN) was first approved by the FDA in 1988, and it is still regarded as the treatment of choice for MRSA. The efficacy of VAN treatment has become less effective due to the development of VAN resistance in MRSA and the potential for nephrotoxicity. This study aims to improve the efficacy of VAN treatment by identifying the folate receptor for MRSA infected tissues and developing folate decorated lipid nanoparticles containing VAN (LVAN). In comparison to conventional VAN, LVAN showed a higher bactericidal effect and a superior ability to inhibit biofilm in MRSA with an enhanced accumulation in MRSA infected thigh tissues and a reduced accumulation in kidney. The results suggested that LVAN is a promising candidate to overcome the current limitations of bacterial resistance and adverse side effects in kidneys found in VAN.